2017
DOI: 10.16943/ptinsa/2017/49126
|View full text |Cite
|
Sign up to set email alerts
|

Calendula Officinalis-An Important Medicinal Plant with Potential Biological Properties

Abstract: Calendula officinalis L. (Marigold) is globally known for its medicinal importance containing various phyto-chemicals including carbohydrates, amino acids, lipids, fatty acids, carotenoids, terpenoids, flavonoids, quinones, coumarins and other constituents, showing some important biological activities like wound healing, immuno-stimulant, spasmogenic and spasmolytic, hepatoprotective, genotoxic and antigenotoxic, anti-amylase, anti-inflammatory, anti-oedematous, anti-bacterial and anti-fungal, antioxidant, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
0
29
0
5
Order By: Relevance
“…The flowers of Calendula officinalis , known as pot marigold, are used in traditional folk medicine in the preparation of aqueous extract, ointments, among others, especially for treating inflammations and wounds [11]. Jan et al [12] reported that C. officinalis is an important medicinal plant with diverse phytochemicals and biological activities, such as antioxidant, anti-inflammatory, antibacterial, gastroprotective, and hepatoprotective. Among the phytochemicals present in flowers of C. officinalis , the triterpenes [13], flavonoids [13,14,15], phenolic acids [13,15], quinones and coumarins [16], and carotenoids [16,17] stand out.…”
Section: Introductionmentioning
confidence: 99%
“…The flowers of Calendula officinalis , known as pot marigold, are used in traditional folk medicine in the preparation of aqueous extract, ointments, among others, especially for treating inflammations and wounds [11]. Jan et al [12] reported that C. officinalis is an important medicinal plant with diverse phytochemicals and biological activities, such as antioxidant, anti-inflammatory, antibacterial, gastroprotective, and hepatoprotective. Among the phytochemicals present in flowers of C. officinalis , the triterpenes [13], flavonoids [13,14,15], phenolic acids [13,15], quinones and coumarins [16], and carotenoids [16,17] stand out.…”
Section: Introductionmentioning
confidence: 99%
“…[ 34 , 35 , 36 , 37 , 38 , 39 ]. Calendula officinalis flower extract, owing to its complex composition ( Figure 1 ), possess multiple activities, including antioxidant, antibacterial, antifungal, antiviral, anti-inflammatory, antioedematous, and wound healing activities, as well as immunostimulant, anticancer, hepatoprotective, and insecticidal properties [ 40 , 41 , 42 , 43 , 44 , 45 ]. For these reasons, pot marigold is used in the treatment of numerous skin injures, such as burns, ulcers, skin inflammations, eczema, bruises, cuts, and abrasions of the epidermis, rashes, skin wounds, frostbites, and other conditions [ 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several classes of biochemical compounds were identified in C. officinalis inflorescences including essential oil, carotenoids, flavonoids, terpenoids, coumarins, quinones, amino acids, lipids, and carbohydrates. These compounds can be used for various pharmaceutical and medicinal purposes: as an anti-oxidant, anti-inflammatory, anti-bacterial, anti-fungal, anti-cancer, anti-HIV, to promote wound healing, and more (Khalid and da Silva, 2012;Jan and John, 2017;Cruceriu et al, 2018;Verma et al, 2018;Givol et al, 2019).…”
Section: Introductionmentioning
confidence: 99%